First evaluation steps of a new method for dietary intake estimation regarding a list of key food groups in adults and in different sociodemographic and health-related behaviour strata - Béjar, Luis M (Public health nutrition, 2017)
A new method known as 'current-day dietary recall' (current-day recall) is based on an application for mobile phones called 'electronic 12 h dietary recall' (e-12HR). This new method was designed to rank participants into categories of habitual intake regarding a series of key food groups. The present study compared current-day recall against a previously validated short paper FFQ. Participants recorded the consumption of selected food groups using e-12HR during twenty-eight consecutive days and then filled out a short paper FFQ at the end of the study period. To evaluate the association and agreement between both methods, Spearman's correlation coefficients (SCC), cross-classification analysis and weighted kappa statistics (κ w) were used. Andalusia, Spain, Southern Europe. University students and employees over the age of 18 years. One hundred and eighty-seven participants completed the study (64·2 % female, 35·8 % male). For all particpants, for all food group intakes, the mean SCC was 0·70 (SCC≥0·62 were observed for all strata); the mean percentage of participants cross-classified into categories of 'exact agreement+adjacent' was 90·1 % (percentages≥87·8 % were observed for all strata); and the mean κ w was 0·55 (κ w≥0·53 in ten of the twelve strata). For the whole sample and for all strata thereof, the current-day recall has good agreement with the previously validated short paper FFQ for assessing food group intakes, rendering it a useful method for ranking individuals.